Pengaruh Ekstrak Metanol Daun Kayu Kuning (Arcangelisia flava (L.) Merr.) terhadap Kadar Kolesterol Total dan Trigliserida Tikus Hiperlipidemia (The Influence of Methanol Extract of Yellow Root (Arcangelisia flava (L.) Merr.) Leaves on Total Cholesterol - Putri Eka Maryani; Evi Umayah Ulfa; Ema Rachmawati (Pustaka Kesehatan, 2016)
Hyperlipidemia is heterogeneous disorder that characterized by elevated levels of total cholesterol, low density lipoprotein (LDL), very low density lipoprotein (VLDL), triglyceride, and decreased levels of high density lipoprotein (HDL). The aim of this study was to determine the ability of methanol extract of leaves of Arcangelisia flava to decrease total cholesterol and triglyceride in some variations of dosage. Five groups experimental animal (each consisting of 4 rats) which have been induced by high fat and fructose diet for 45 days, followed by oral treatment of extract at a dose of 250 mg/kg BW, 500 mg/kg BW, 750 mg/kg BW, simvastatin 0.36 mg/200 g BW (control (+)), and CMC Na 1% (control (-)) for 7 days. The blood was taken on day 8, then was measured the total cholesterol and triglyceride. The test results showed that extract could decrease total cholesterol and triglyceride in line with increasing doses. According to ANOVA, there are significant differences between treatment groups (p